(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Analysis of some factors affecting compliance with regulations on private medical examination and treatment of specialized clinics in Son La city in 2023. Objective: Analyze some factors affecting compliance with regulations on private medical examination and treatment of specialized clinics in Son La city in 2023. Subjects and methods: Direct staff Participate in the management of the Medical Operations Department and the Inspection Department under the Department of Health; Person in charge of expertise of the private medical examination and treatment of specialized clinics in Son La City. Conducted 04 in-depth interviews with 02 officers at the Medical and Pharmaceutical Operations Department and the Inspection Department of the Health Department, 01 leader of Son La Health Department and 01 Health Center leader of Son La city. Conducted 10 in-depth interviews with 10 peope in charge of expertise of private medical examination and treatment of specialized clinics. Results: Some factors affecting the practice of natural conservation: Improving the knowledge and attitudes of person in charge of expertise has a positive influence on compliance with regulations through training and propaganda for natural conservation practitioners. . Management, inspection and examination have a positive impact on the implementation of legal regulations. Current legal documents and instructions are not specific and have many inadequacies that cause difficulties for establishments and need to be corrected. The assignment of management to medical examination and treatment facilities is incomplete and lacks coordination. The health inspection force is too thin and lacks close attention, affecting management. Limited revenue from medical examination and treatment makes it difficult to meet regulatory requirements. The consequences of the covid-19 epidemic have a negative impact on establishments’ compliance with legal regulations. The ongoing revision of the Law on Medical Examination and Treatment is also a factor affecting compliance with the law. Conclusion: Raising awareness of practitioners through forms of communication, dissemination of legal documents, etc. Advising on the development of documents, regulations and instructions on the management of private medical examination and treatment locality.